Quantitative Evaluation of a Mexican and a Ghanaian Tabernaemontana Species as Alternatives to Voacanga africana for the Production of Antiaddictive Ibogan Type Alkaloids. Issue 5 (29th April 2020) - Krengel, Felix; Dickinson, Jonathan; Jenks, Christopher; Reyes‐Chilpa, Ricardo
Abstract: In continuation of our efforts to provide quantitative information on antiaddictive ibogan type alkaloid‐producing Tabernaemontana species, we used gas chromatography‐mass spectrometry (GC/MS) to compare the alkaloid profiles of the barks and/or leaves of one Mexican and one African species – T. arborea and T. crassa, respectively, with the primary sources of commercially available semisynthetic ibogaine, Voacanga africana root and stem bark. The qualitative and quantitative similarities between T. arborea and V. africana barks consolidate previous reports regarding the potential of the former as a promising alternative source of voacangine and ibogaine. The results also suggest that T. crassa could be used to produce conopharyngine and ibogaline, two compounds with the same basic skeletal structure and possibly similar antiaddictive properties as ibogaine. Abstract :